Pengaruh Mekanisme Good Corporate Governance, Leverage, dan Profitabilitas pada Manajemen Laba - Sukrasta, Ni Komang Meilantari; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2025)
This study aims to examine the effect of mechanisms Good Corporate Governance, leverage, and profitability on earnings management. The research population is non-financial companies with the consumer noncyclicals sector listed on the Indonesia Stock Exchange for the period 2018-2021. The total sample of 19 companies was selected by purposive sampling technique. The analysis technique used is multiple linear regression analysis with the help of SPSS 26 software. The results of study show that leverage has a positive effect on earnings management. Contrary to the research hypothesis, the results of the analysis in this study show that the mechanism of Good Corporate Governance and profitability have no effect on earnings management. Keywords: Agency Theory; Accounting Positive Theory; Good Corporate Governane; Leverage; Profitability; Earnings Management